2021
DOI: 10.3390/s21103316
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Strategy for Automatic Sleep Staging Based on Two-Channel EEG Headband Data

Abstract: Sleep disturbances are common in Alzheimer’s disease and other neurodegenerative disorders, and together represent a potential therapeutic target for disease modification. A major barrier for studying sleep in patients with dementia is the requirement for overnight polysomnography (PSG) to achieve formal sleep staging. This is not only costly, but also spending a night in a hospital setting is not always advisable in this patient group. As an alternative to PSG, portable electroencephalography (EEG) headbands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Based on signal measured with ear-EEG electrodes, random forest classifier has been used to achieve scoring accuracies of κ = 0.45-0.65 [24] and κ = 0.73 [25]. A fabric headband with forehead electrodes developed by Cognionics Inc. (San Diego, CA, USA) has been recently used to achieve 74.0% deep learning scoring accuracy based on two-channel data [26]. Furthermore, a commercially available device, Dreem headband (Dreem Inc., Paris, France), has been used to achieve 83.5% (κ = 0.748) accuracies with a deep learning model that was trained with consensus hypnograms of five experienced scorers [4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on signal measured with ear-EEG electrodes, random forest classifier has been used to achieve scoring accuracies of κ = 0.45-0.65 [24] and κ = 0.73 [25]. A fabric headband with forehead electrodes developed by Cognionics Inc. (San Diego, CA, USA) has been recently used to achieve 74.0% deep learning scoring accuracy based on two-channel data [26]. Furthermore, a commercially available device, Dreem headband (Dreem Inc., Paris, France), has been used to achieve 83.5% (κ = 0.748) accuracies with a deep learning model that was trained with consensus hypnograms of five experienced scorers [4].…”
Section: Discussionmentioning
confidence: 99%
“…We removed data only in the corrupted channel, duplicating the valid channel in its place. We then passed the EEG into 12 deep learning models, previously described, 11 each trained on a different overlapping subset of labelled data. Majority voting was used to predict the 12 models, keeping the majority prediction for epochs in which ≥7 models agreed, labelling epochs for which the majority of the models did not agree as “unknown.”…”
Section: Methodsmentioning
confidence: 99%
“…We used a commercially available EEG headband (Cognionics Inc.) customized for two-channel recordings, as previously described. 11 The headband was also made to use disposable clip-on Kendall Meditrace Mini adhesive hydrogel foam electrodes (Cardinal Health). Detailed picture instructions on where to attach the electrodes at home were given.…”
Section: Eeg Acquisitionmentioning
confidence: 99%
“…Studies led by Ma et al suggested that deep learning methods achieve robust sleep staging results of both portable and in-hospital EEG recordings. In addition, it may allow for more widespread use of ambulatory sleep assessment tests across a variety of clinical conditions, including neurodegenerative disorders ( 48 ). The diagnostic accuracy of a novel algorithm for the estimation of sleep stages and disease severity in patients with breathing-disordered sleep is based on actigraphy and respiratory inductance plethysmography ( 49 ).…”
Section: Alternative Sleep Monitoring In Nementioning
confidence: 99%